Alternatives to neoliberalism : towards equality and democracy / edited by Bryn Jones and Mike O'Donnell ; foreword by Sylvia Walby. - Jones, Bryn, 1946-; O'Donnell, Mike (Policy Press, 2017)
With contributions from innovative social and policy analysts including Colin Crouch, Anna Coote, Grahame Thompson and Ted Benton, this collection provides a revised framework for social democracy.